2020
DOI: 10.1177/1756284820937089
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-operative biologic therapy on post-operative surgical outcomes in ulcerative colitis: a systematic review and meta-analysis

Abstract: Background and aims: Biologic therapy has emerged as an effective modality amongst the medical treatment options available for ulcerative colitis (UC). However, its impact on post-operative care in patients with UC is still debatable. This review evaluates the risk of post-operative complications following biologic treatment in patients with UC. Methods: A systematic search of the relevant databases was conducted with the aim of identifying studies that compared the post-operative complication rates of UC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The risk of postoperative infection or complication may be increased with the use of immunomodulatory biologics [ 40 ]. While studies evaluating this risk have been conducted, most have been in other disease states (e.g., rheumatoid arthritis and ulcerative colitis) or with biologics with different mechanisms of action, such as tumor necrosis factor- α inhibitors (e.g., infliximab and etanercept) [ 40 , 41 ]. There is currently no evidence to support the concern that biologics used in severe asthma and allergic conditions increase the risk of postsurgical complications; as such, on the basis of clinical expert opinion, the dose of the biologics for severe asthma and allergic conditions does not need to be withheld in preparation for surgery or postsurgery and will more likely reduce postoperative respiratory complications.…”
Section: Results and Discussion Section 1: When To Withhold Biologic ...mentioning
confidence: 99%
“…The risk of postoperative infection or complication may be increased with the use of immunomodulatory biologics [ 40 ]. While studies evaluating this risk have been conducted, most have been in other disease states (e.g., rheumatoid arthritis and ulcerative colitis) or with biologics with different mechanisms of action, such as tumor necrosis factor- α inhibitors (e.g., infliximab and etanercept) [ 40 , 41 ]. There is currently no evidence to support the concern that biologics used in severe asthma and allergic conditions increase the risk of postsurgical complications; as such, on the basis of clinical expert opinion, the dose of the biologics for severe asthma and allergic conditions does not need to be withheld in preparation for surgery or postsurgery and will more likely reduce postoperative respiratory complications.…”
Section: Results and Discussion Section 1: When To Withhold Biologic ...mentioning
confidence: 99%
“…37 Furthermore, a recent meta-analysis on postoperative infection with anti-TNF inhibitors found that the risk of postoperative infection was increased in patients with CD on anti-TNF agents but not for patients with UC on anti-TNF agents. 38…”
Section: Preoperative Periodmentioning
confidence: 99%
“…37 Furthermore, a recent meta-analysis on postoperative infection with anti-TNF inhibitors found that the risk of postoperative infection was increased in patients with CD on anti-TNF agents but not for patients with UC on anti-TNF agents. 38 The data on vedolizumab on postoperative morbidity were conflicting. A single-center, retrospective review compared vedolizumab-exposed patients with CD with patients on anti-TNF or biologic-naive patients and found vedolizumab to be an independent predictor of postoperative surgical site infection.…”
Section: Preoperative Use Of Biologicsmentioning
confidence: 99%
“…However, in comparison with the general population, the 5-year surgery rates with its accompanying potential postoperative complications remain substantial for IBD patients. [ 2 ] Previously conducted meta-analyses, analyzing the effect of preoperative anti-TNF-α treatment on postoperative complications has reported conflicting findings [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is mostly the result of including different preoperative drug withdrawal periods in the analyses. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] In order to find consistent values regarding the effect of preoperative anti-TNF-α treatment on postoperative complications and to ensure better comparisons of data, we chose the objectifiable anti-TNF-α drug washout period of 12 weeks [ 18 ] as the preoperative cut-off value in this analysis.…”
Section: Introductionmentioning
confidence: 99%